Investigation of different hydrogels for nucleus replacement : a biomechanical study - Reitmaier, Sandra (2012)
Hydrogels are considered promising for disc regeneration strategies. However, it is currently unknown whether the destruction of the natural interface between nucleus and surrounding structures caused by nucleotomy and an inadequate annulus closure diminishes the mechanical competence of the disc. To clarify these mechanisms and to evaluate whether hydrogels are able to restore the biomechanical behaviour of the disc a combined in vivo and in vitro and approach was used.